An Innovative Balanced-Yielding Support Method for Tunnel in Deep Inclined Strata. (17th August 2022) - Yongke, Wei; Hongyan, Guo; Juyi, Hu; Jiaqing, Liu; Limin, Liu
Abstract : Aiming at the problem that the uneven deformation of the tunnel surrounding rock in the deep inclined rock strata caused local instability, an innovative balanced-yielding support technology was proposed with the engineering background of the Shangping tunnel in Huafeng Mine. Based on the mechanism analysis of this technology, the specific implementing steps were proposed. It mainly included in situ stress analysis, the stress distribution of the tunnel surrounding rock with different sections, the design of the parameter of bolt-cable and yielding structure, and supporting effect evaluation. The results showed that (1) the stress concentration appeared at the top corners of the lower side and the bottom corner of the upper side of the rectangular and semicircular arched tunnel. (2) Compared with rectangle and vertical-wall semicircular arch tunnels, the trapezoidal tunnel could relieve the shearing effect of the inclined rock strata. (3) The length, prestress, spacing-row distance of the bolt, and the parameter of the yielding structure were all optimally designed to form the balanced-yielding support system. (4) In engineering application, the maximum deformations of the roof, right side and left side, were less than 80 mm. Compared with the original support system, the shallow separation of the trapezoidal tunnel supported by the balanced-yielding support system had been reduced by 147%.